2017
DOI: 10.1186/s13102-017-0080-2
|View full text |Cite
|
Sign up to set email alerts
|

Could current factors be associated with retrospective sports injuries in Brazilian jiu-jitsu? A cross-sectional study

Abstract: BackgroundBrazilian jiu-jitsu is characterized by musculoskeletal disorders and high occurrence of sports injuries. The present study was aimed to analyze some internal factors, as well as to describe occurrence and characteristics of retrospective musculoskeletal injuries in different age groups of Brazilian jiu-jitsu practitioners.MethodsOne hundred ninety-three Brazilian jiu-jitsu practitioners, which were divided into three age groups: Adolescent, Adult, and Master. Besides anthropometric characterization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
2
16
0
3
Order By: Relevance
“…In the present study, there was a high prevalence of MSK-I (76%) among Brazilian rugby, soccer, combat, handball and water polo athletes, and 19% reported a history of tendinopathy and joint and muscle injuries in combination. Our result is in agreement with that of Graças and colleagues, who observed a prevalence of 82.6% of MSK-I in Brazilian jiu-jitsu athletes [16]. In addition, 65% of first division soccer athletes showed some MSK-I type during the season [17], and 58% of university athletes from fifteen different sports had at least one injury at the end of the sports season [18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, there was a high prevalence of MSK-I (76%) among Brazilian rugby, soccer, combat, handball and water polo athletes, and 19% reported a history of tendinopathy and joint and muscle injuries in combination. Our result is in agreement with that of Graças and colleagues, who observed a prevalence of 82.6% of MSK-I in Brazilian jiu-jitsu athletes [16]. In addition, 65% of first division soccer athletes showed some MSK-I type during the season [17], and 58% of university athletes from fifteen different sports had at least one injury at the end of the sports season [18].…”
Section: Discussionsupporting
confidence: 93%
“…Age-adjusted logistic regression analyses have shown that athletes who train more than 2 h per day are 2 to 3.5 times more likely to develop an MSK-I, mainly in sports involving overuse or repetitive movements [32]. In addition, this result is in consonance with a Brazilian study, which observed a higher occurrence of MSK-I in jiu-jitsu athletes aged 30 years or more [16], and with the study of Snodgrass and colleagues, in which age was associated with muscle-tendon injury history in the neck in Australian rugby union players [33]. This can support further analytical studies by creating surveillance programmes to increase the career duration of athletes.…”
Section: Discussionsupporting
confidence: 75%
“…The development of the sports discipline of Brazilian jiu-jitsu (BJJ) and its increasing popularity was followed by an increasing number of publications on the physical and physiological pro le of BJJ athletes [1], on the biomechanics aspects of the athletes [2], on the technical and tactical analyses [3,4], and on the incidence of injuries [5][6][7][8]. Brazilian jiu-jitsu (BJJ) is a type of martial art and as such it requires certain physical and physiological qualities, such as mesomorphic somatotype, aerobic and anaerobic power, muscle power and endurance and exibility [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Most papers available from the literature on BJJ discuss professional athletes [5,6]. In the literature only two papers were available, which focused on the athletes who did BJJ both non-professionally and/ or recreationally [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…With a significant population of BJJ participants older than 30, there is an opportunity to analyze concussions in a population that are studied less frequently [ 4 ]. It has been shown that musculoskeletal injuries in BJJ occur more frequently in practitioners over age 30, although there has been no research published on brain injuries in this age group [ 13 ]. Outside of BJJ, there is evidence that females are more likely to suffer concussions in a given sport than their male counterparts [ 12 ].…”
Section: Introductionmentioning
confidence: 99%